1H MR spectroscopy of mesial temporal lobe epilepsies treated with Gamma knife - Hájek, Milan; Dezortová, Monika; Liscák, Roman; Vymazal, Josef; Vladyka, Vilibald (European radiology, 2003)
Proton MR spectroscopy was used to observe long-term post-irradiation metabolic changes in epileptogenic tissue and in the contralateral parts of the brain which are not available with conventional imaging methods. We studied these changes in the temporal lobe in six patients, following radiosurgery on the amygdala and hippocampus. (1)H MR spectroscopy at 1.5 T with short and long echo times (TE=10 and 135 ms) were used together with standard MR imaging sequences (T1-, T2-weighted). The treatment was performed by Leksell Gamma Knife with a dose of 50 Gy to the center and a 50% isodose to the margin of the target, represented by the mean volume of approximately 7.5 ml. Magnetic resonance imaging and MR spectroscopy examinations were performed at least once per year for 3 years. The most significant changes in spectra were observed approximately 1 year after the irradiation when edema in irradiated area was observed and strong signal of lipids was identified. Later, edema and lipid signals disappeared and follow-up was characterized by a decrease of NAA, Cr, and Cho concentrations in the ipsilateral region of the brain to the irradiation (LCModel calculation from voxel of interest 3.8-4.5 ml positioned into the centrum of target volume). The concentration of NAA, Cr, and Cho after radiosurgery was significantly different from control values ( p<0.05) and also from concentrations in the contralateral part of the brain ( p<0.05). In the contralateral part, the concentration of NAA was significantly increased ( p<0.05) (NAA: before treatment 8.81, after treatment 11.33 mM). No radiotoxic changes were observed in the contralateral part of the brain or behind the area of target volume. The MR spectroscopy findings precluded MRI observation and MRS results completed data about the development of radiotoxic changes in the target volume.
Keywords: Seizures; Magnetic Resonance Imaging; metabolismus lipidů; nádory mozku; radiační poranění; mozek; magnetická rezonanční tomografie; Humans; tolerance záření; Brain Neoplasms; Lipid Metabolism; Choline; kreatin; epilepsie temporálního laloku; Female; Glutamic Acid; dospělí; záchvaty; Glutamine; lipidy; Radiation Injuries; kyselina asparagová; lidé; magnetická rezonanční spektroskopie; glutamin; cholin; časové faktory; Creatine; radiochirurgie; Adult; Postoperative Complications; Radiosurgery; pooperační komplikace; Follow-Up Studies; ženské pohlaví; Male; Brain; Epilepsy, Temporal Lobe; Lipids; Aspartic Acid; Radiation Tolerance; Magnetic Resonance Spectroscopy; Treatment Failure; mužské pohlaví; Time Factors; neúspěšná terapie; následné studie; kyselina glutamová